Bain's Theory of Moral Judgment and the Development of Mill's Utilitarianism. Issue 4 (December 2022) - Zimmerman, Aaron
Abstract: In Utilitarianism, Mill defers to Alexander Bain's expertise on the subject of moral judgment to answer common criticisms of the creed. First, we do not blame people or label them immoral when they are less than ideal. Judgments of immorality are commonly reserved for substandard behavior, not suboptimal comportment. Second, we do not commonly insist on full neutrality in benevolence. Indeed, some philosophers argue that we are obliged to exhibit partiality, insofar as it is demanded by our roles as friends, parents, or children. My primary aim in this essay is to explicate Bain's theory of moral judgment and explain how Mill used Bain's psychological doctrines to inform his development of an indirect utilitarian moral philosophy, immune to the criticisms described above.